Interlinguistic Correspondence And Semantic Transfer Of Phytonymic Phraseological Units In English And Uzbek Languages (Texas Journal of Philology, Culture and History, 2025)
The study of interlingual phraseological correspondences has always been of great theoretical and practical importance, so many scientists are interested in the issue of finding and identifying them. Naturally, interlingual correspondences are required, first of all, in the translation process, when transferring from one language to another. Comparative study of phraseological units with a phytonymic component in two languages is important not only for translation practice, but also for determining their semantic structure, conceptual model and linguocultural characteristics. “Translation problems” are used here not as a goal, but as a method of linguistic analysis: that is, the deep layers of meaning are revealed through how a phytophraseoema from one language is transferred to another.